African Americans in the post-emancipation South : the outsiders' view - Hornsby, Alton (University Press of America, 2010)
This study uses first-hand accounts and documents to view African American life in the post-emancipation South. Spanning from the 1860s through the New Deal this study incorporates a broad cross-section of the views of European travelers and Euro-American visitors from the North. The study synthesizes the outsiders' observations and assesses their summaries' overall validity for increasing our understanding of the lives of blacks in the post-emancipation South. These accounts allow for a reconstruction of African American life and labor in the major aspects of black culture.